A conceptual framework for determinants of customer satisfaction of fixed-line telecom services in Pakistan - Mahessar, Imtiaz Hussain; Keerio, Imran Khan; Ali Shah, Masoomi Hifazat; Shah, Asadullah; Rind, M Malook; Qureshi, Imran Ahmed; Luhana, Krishan Kumar (IEEE, 2023)
With the progression of communication technologies, there has been a decline in people's utilization of fixed-line telephones. It is essential to ascertain the fundamental causes underlying this phenomenon. There are numerous assumptions that service providers tend to favor their interests. Gaining an understanding of the factors that contribute to client satisfaction may require a significant investment of effort. Consequently, this study aims to ascertain the determinants that impact consumers' happiness with their fixed-line telecommunications service. In order to achieve the objectives of the research, a theoretical framework is presented whereby consumer satisfaction is considered the dependent variable. At the same time, responsiveness, perceived value, perceived service quality, and staff attitude are regarded as independent variables. The primary objective of this study is to ascertain the key factors that significantly influence Customer Satisfaction with Fixed-Line Telecom Services in Pakistan.